71°- domain wall in cubic crystal with photoinduced magnetic anisotropy - Antoniuk, O.A.; Kovalenko, V.F.; Tychko, O.V. (Functional Materials, 2004)
The influence of photoinduced anisotropy on Bloch 71°-domain wall in cubic magnetically ordered (100) crystal with negative constant of cubic magnetic anisotropy is studied. Equilibrium domain wall parameters (the surface energy density, orientation, and effective width) of the- wall have been found as functions of parameters (the constant value and easy axis orientation) of the photoinduced magnetic anisotropy. The energy density of the domain wall has been shown to be able both to increase and decrease, depending on the crystal irradiation conditions. Вивчається вплив фотоіндукованої магнітної анізотропії на 71°-плоску блохівську доменну границю в кубічному магнітовпорядкованому (100)-кристалі з від’ємною кон-стантею кубічної магнітної анізотропії. Знайдено рівноважні параметри досліджуваної доменнї границі (поверхневу густину енергії, орієнтацію та ефективну ширину) в залежності від параметрів (значення константи та орієнтації легкоїосі) фотоіндукованої магнітної анізотропії. Показано, що густина енергії так°ї доменної границі може як зростати, так і зменшуватися в залежності від умов опромінення кристалу. Изучается влияние фотоиндуцированной магнитной анизотропии на 71°- плоскую блоховскую доменную границу в кубическом магнитупорядоченном (100)-кристалле с отрицательной константой кубической магнитной анизотропии. Найдены равновесные параметры исследуемой доменной границы (поверхностная плотность энергии, ориентация и эффективная ширина) в зависимости от параметров (значение константы и ориентация легкоси) фотоиндуцированной магнитой анизотропии. Показано, что плотность энергии такой доменной границы может как возрастать, так и уменьшаться в зависимости от условий облучения кристалла.